The Role of Non-Directive Supervision in Teacher Career Development and Educational Professionalism - Khasanah, Aminatul Isnaeni (Jurnal Administrasi Pendidikan Islam, 2024)
Increasing educational professionalism and teacher career development has become the main focus in efforts to improve the quality of education throughout the world. One approach that is increasingly recognized is non-directive supervision. This research aims to investigate the role of non-directive leadership in teacher career development and educational professionalism. This research uses a qualitative approach with a literature study. The results of this research reveal that non-directive supervision provides an environment that supports teachers in identifying and overcoming challenges in their teaching practices. This approach provides space for personal reflection and professional growth, which, in turn, influences teacher career development. These findings indicate that non-directive supervision not only contributes to improving teacher performance but also strengthens educational professionalism. Additionally, this approach helps create positive relationships between supervisors and teachers, encouraging collaboration and shared learning. This research concludes that non-directive supervision is important in improving teacher career development and educational professionalism. These findings imply that schools and educational institutions need to consider the integration of non-directive supervision in their efforts to improve the quality of education and support teacher professional growth.